ChemInform Abstract: Iterative Reactions of Transient Boronic Acids Enable Sequential C—C Bond Formation. Issue 26 (June 2016) - Battilocchio, Claudio; Feist, Florian; Hafner, Andreas; Simon, Meike; Tran, Duc N.; Allwood, Daniel M.; Blakemore, David C.; Ley, Steven V.
Abstract: A metal‐free approach towards iterative C—C bond formation sequences is developed.